New M-Type Periodic Variables Of Catalina Sky Survey Database - Kostandyan, G. R.
In this paper we continue spectral class determinations for optically faint periodic variables from Catalina Sky Survey (CSS) database for which P  10 days. Based on Gaia Data Release 3 (DR3) BP/RP spectroscopic data base 169 objects are confirmed as G and K-type stars, 78 objects are confirmed as M-type stars. We have constructed the color-absolute M(G) magnitude (CaMD) diagram and 2MASS data J-H versus H-Ks color-color diagram for new 78 M type stars. By analyzing the two diagrams and Transiting Exoplanet Survey Satellite (TESS) data, we can conclude that 74 objects are M giants and 4 objects are M dwarfs. The ASAS-SN phase dependence light curves analysis confirms 47 stars as Mira-type variables, 25 as Semi-Regulars (SR), two objects as Irregular (IR)-type variables and 4 as Rotating variables (ROT). Two M type dwarfs and 34 giants, show Spectral Energy Distribution (SED) with infrared excess, indicating the existence of circumstellar envelope around them.
Keywords: Astrophysics